2022
DOI: 10.32598/ijpcp.28.1.3788.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Personality Organization, Job Stress, and Ego Strength on Audit Quality

Abstract: Objectives: The purpose of this study was to investigate the effect of personality organization, job stress and ego strength on predicting audit quality in auditing organizations and independent audit companies. Method: The statistical population of this study is all auditors of the audit organization with 191 individuals and independent audit companies with 208 companies, which included at least 3 auditors in 2019, which finally constituted 815 people in the statistical population. 261 individuals were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Such that, Mahmudi et al (2022) found, auditor work stress pressure has a negative and significant effect on audit quality. Also, Nasirpour et al (2022) found job stress had a significant and inverse impact on the audit quality of auditors of independent audit companies.…”
Section: Introductionmentioning
confidence: 96%
“…Such that, Mahmudi et al (2022) found, auditor work stress pressure has a negative and significant effect on audit quality. Also, Nasirpour et al (2022) found job stress had a significant and inverse impact on the audit quality of auditors of independent audit companies.…”
Section: Introductionmentioning
confidence: 96%